2002
DOI: 10.1046/j.1523-1755.2002.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of lipids in urine, crystals and stones: Implications for the formation of kidney stones

Abstract: Stone forming conditions in the kidneys greatly impact their epithelial cells producing significant differences in the urinary lipids between healthy and stone forming individuals. Altered membrane lipids promote face selective nucleation and retention of calcium oxalate crystals, and in the process become a part of the growing crystals and stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 38 publications
2
95
0
4
Order By: Relevance
“…Interestingly, in 2002 Khan et al reported [2] that urolithic patients excrete more lipids such as total cholesterol, triglycerides, and some phospholipids [2]. The same study further suggested that lipids modulate the calcium oxalate crystal nucleation, aggregation and retention processes, which are the important steps for kidney stone development [2].…”
Section: Dear Editormentioning
confidence: 88%
See 3 more Smart Citations
“…Interestingly, in 2002 Khan et al reported [2] that urolithic patients excrete more lipids such as total cholesterol, triglycerides, and some phospholipids [2]. The same study further suggested that lipids modulate the calcium oxalate crystal nucleation, aggregation and retention processes, which are the important steps for kidney stone development [2].…”
Section: Dear Editormentioning
confidence: 88%
“…On the other hand, the association of kidney stones and subclinical carotid atherosclerosis has been observed in young adults implying that renal lithogenesis and atherogenesis share common pathophysiology both systemically and on a cellular level [3], where oxalate would act as a pro-atherogenic factor to increase the oxidative stress [2] as seen in atherosclerosis patients [3]. Injury and retention model explains the lithogenesis and atherogenesis [2,3].…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Számos tanulmány utal arra, hogy a húgyúti kövesség-ben szenvedő betegek körében gyakoribb a dyslipidaemia, valamint, hogy a lipideknek szerepük van az oxalát-kiválasztódás növekedésében, ami telített zsírsavakban és transzzsírsavakban (például arachidonsav) gazdag étel fogyasztása esetén még kifejezettebb [25][26][27]. Az arachidonsav a prosztaglandin-E2-szint növekedését okozza, ami hozzájárul a hypercalciuria kialakulásához, és elősegíti a csontállomány kalciumvesztését [28].…”
Section: Zsírbevitelunclassified